Field Data-based Mathematical Simulation Of Manual Rebar Cutting - Mishra, Satya Prakash; Parbat, Dhananjay K.; Modak, Jayant P. (Penerbit Universiti Sains Malaysia, 2014)
Construction process activities are very complex in nature and there have been attempts to simulate them via numerous methods. Manual work, which constitutes a large proportion of total construction in India and developing countries, requires emphasis. Field data-based mathematical simulations develop an empirical relation between inputs and outputs; once the model is developed and weaknesses have been identified, methods can be easily improved and optimised for output goals. This paper covers in detail the process of developing models for the rebar cutting subactivity of reinforced concrete construction in residential buildings. These models are evaluated using sensitivity analysis, optimisation techniques and reliability analysis and are validated using artificial neural networks.